Printed circuit board and method for preparing the same
By forming a specific surface roughness area on the dielectric layer of the printed circuit board and forming an adhesive layer, combining micro-nano laser processing and ion sputtering, the problem of insufficient peeling strength between the dielectric layer and the conductive line layer is solved, and the problem of insufficient peeling strength between the dielectric layer and the conductive line layer is realized. It takes into account both low signal transmission loss and high peel strength.
Patent Information
- Application Number
- CN202210763790.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-30
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2042-06-30
AI Technical Summary
While reducing signal transmission losses, traditional printed circuit boards are difficult to ensure high peel strength between the dielectric layer and the conductive line layer, resulting in unstable signal transmission.
By forming a first area with a surface roughness of 0.3 μm-1.0 μm on the dielectric layer, and forming an adhesive layer in this area, combining micro-nano laser treatment and ion sputtering method, a conductive line layer is formed to ensure the dielectric layer. High peel strength with the conductive line layer while reducing dielectric loss.
The high peel strength between the dielectric layer and the conductive line layer is achieved, which reduces the signal transmission loss of the printed circuit board and meets the application scenarios of extremely low signal transmission loss.
Smart Images

Figure BDA0003724837480000161
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electronic industry, in particular to a printed circuit board and a preparation method thereof. Background Art
[0002] A traditional printed circuit board includes a stacked dielectric layer and a conductive circuit layer. In order to ensure the integrity of the signal transmitted by the printed circuit board, it is necessary to reduce the signal transmission loss of the printed circuit board. The signal transmission loss of the printed circuit board is mainly affected by the dielectric loss of the dielectric layer and the conductor loss of the conductive circuit layer.
[0003] In order to reduce the signal transmission loss of printed circuit boards, the traditional method is to add a resin with lower polarity or a dielectric filler with a smooth surface and higher purity to the dielectric layer to reduce the surface roughness of the dielectric layer, thereby reducing dielectric loss; or optimize the copper nodule process to reduce conductor loss. However, both of the above methods have the problem of high technical development difficulties and difficulty in ensuring the peel strength between the dielectric layer and the conductive circuit layer. Summary of the invention
[0004] Based on this, it is necessary to provide a printed circuit board and a preparation method thereof to address the above-mentioned problems; the preparation method can reduce the signal transmission loss of the printed circuit board, while ensuring a high peel strength between the dielectric layer and the conductive circuit layer, so that the printed circuit board can better meet application scenarios such as extremely low signal transmission loss.
[0005] The present invention provides a printed circuit board, comprising a dielectric layer, and an adhesive layer and a conductive circuit layer stacked on at least one surface of the dielectric layer, the area where the dielectric layer and the conductive circuit layer face each other is a first area, and the rest is a second area, the surface roughness of the first area is 0.3 μm-1.0 μm, the surface roughness of the second area is less than or equal to the surface roughness of the first area, and the surface roughness of the second area is less than or equal to 0.5 μm.
[0006] In one embodiment, the dielectric layer is formed by curing one or more semi-cured sheets, and the semi-cured sheets include a reinforcing material and a dried resin composition attached to the reinforcing material. The resin composition includes a thermosetting resin, a low-polarity resin, a dielectric filler and a cross-linking agent, and the solubility parameter of the low-polarity resin is less than or equal to 9.
[0007] In one embodiment, the low polarity resin is selected from polyisoprene, polyisoprene hydrogenated compounds, polyisoprene alkyl compounds, polybutadiene, polybutadiene hydrogenated compounds, polybutadiene alkyl compounds, polystyrene butadiene, polystyrene butadiene hydrogenated compounds, polystyrene butadiene alkyl compounds, butyl rubber, butyl rubber hydrogenated compounds, butyl rubber alkyl compounds, ethylene propylene rubber, ethylene propylene rubber hydrogenated compounds, ethylene propylene rubber alkyl compounds, styrene butadiene ethylene, styrene butadiene ethylene hydrogenated compounds, styrene butadiene ethylene alkyl compounds, styrene butadiene styrene, styrene butadiene ethylene, styrene butadiene ethylene hydrogenated compounds, styrene butadiene ethylene alkyl compounds, styrene butadiene styrene, styrene A copolymer of at least one of ethylene-butadiene-styrene hydrogenated compounds, styrene-butadiene-styrene alkyl compounds, styrene-isoprene-styrene, styrene-isoprene-styrene hydrogenated compounds, styrene-isoprene-styrene alkyl compounds, styrene-ethylene-butylene-styrene, styrene-ethylene-butylene-styrene hydrogenated compounds, styrene-ethylene-butylene-styrene alkyl compounds, styrene-propylene-styrene, styrene-propylene-styrene hydrogenated compounds, styrene-propylene-styrene alkyl compounds, styrene-ethylene-propylene-styrene, styrene-ethylene-propylene-styrene hydrogenated compounds, and styrene-ethylene-propylene-styrene alkyl compounds;
[0008] Alternatively, the low-polarity substance is selected from at least one of fluororubber or its derivatives, silicone rubber, polytetrafluoroethylene or vinyl aromatic compound polymers.
[0009] In one embodiment, the ratio of the sum of the mass of the cross-linking agent and the thermosetting resin to the mass of the low-polarity resin is 20:1-4:1.
[0010] In one embodiment, the solubility parameter of the thermosetting resin is greater than 9, and the thermosetting resin is selected from at least one of thermosetting polyphenylene ether resin, styrene resin, butadiene resin, acrylonitrile-styrene copolymer, methacrylate-styrene copolymer, acrylonitrile-butadiene-styrene copolymer, hydrogenated styrene-butadiene block copolymer, styrene-butadiene-styrene copolymer, styrene-isoprene-styrene copolymer, styrene-polyolefin-styrene copolymer, styrene-acrylonitrile copolymer or styrene-butadiene rubber or nitrile rubber;
[0011] And / or, the mass ratio of the thermosetting resin to the cross-linking agent is 20:80-80:20.
[0012] In one embodiment, the thickness of the adhesive layer is less than or equal to 1.5 μm.
[0013] In one embodiment, the thickness deviation of the bonding layer is less than or equal to 5%.
[0014] In one embodiment, the material of the bonding layer is selected from at least one of a silane coupling agent containing an unsaturated double bond, a silane coupling agent containing an aniline group, a phthalate coupling agent, an aluminate coupling agent, an organic chromium complex coupling agent, a boride, a phosphate, a chromate coupling agent or a stannate coupling agent.
[0015] A method for preparing the printed circuit board as described above comprises the following steps:
[0016] Laminating one or more prepregs to form a prepreg layer, covering at least one surface of the prepreg layer with a tool having a surface roughness of less than or equal to 0.5 μm, and removing the tool after curing to obtain a dielectric layer;
[0017] Performing micro-nano laser processing on a predetermined area of the dielectric layer to form a first area with a surface roughness of 0.3 μm-1.0 μm;
[0018] forming a bonding layer on the surface of the dielectric layer that has been processed by micro-nano laser; and
[0019] A conductive circuit layer is formed at a position directly opposite to the first region to obtain a printed circuit board, wherein the conductive circuit layer is bonded to a surface of the adhesive layer away from the dielectric layer.
[0020] In one embodiment, the step of performing micro-nano laser processing on a preset area of the dielectric layer includes performing micro-nano laser processing on the preset area of the dielectric layer using a pulsed laser, wherein the wavelength of the laser of the pulsed laser is less than or equal to 500 nm, and the laser power of the pulsed laser is less than or equal to 15 W.
[0021] In one embodiment, the step of forming a conductive circuit layer at a position directly opposite to the first region includes forming a conductive circuit layer at a position directly opposite to the first region by using an ion sputtering method.
[0022] In the printed circuit board provided by the present invention, the surface roughness of the second area is less than or equal to 0.5 μm, so that the surface roughness of the first area can be controlled between 0.3 μm and 1.0 μm, and cooperates with the adhesive layer to ensure high peel strength between the dielectric layer and the conductive circuit layer, while reducing the dielectric loss of the printed circuit board, thereby enabling the printed circuit board to better meet application scenarios such as extremely low signal transmission loss.
[0023] In the method for preparing a printed circuit board provided by the present invention, firstly, the surface roughness of the dielectric layer is controlled to be less than or equal to 0.5 μm by controlling the surface roughness of the mold; secondly, the surface roughness of the first region is increased by micro-nano laser processing, thereby cooperating with the adhesive layer to ensure high peel strength between the dielectric layer and the conductive circuit layer, thereby realizing simple preparation of the printed circuit board of the present invention. DETAILED DESCRIPTION
[0024] For ease of understanding of the present invention, the present invention will be described more fully below with reference to relevant embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0026] The printed circuit board provided by the present invention comprises a dielectric layer, and an adhesive layer and a conductive circuit layer stacked on at least one surface of the dielectric layer. The area directly facing the dielectric layer and the conductive circuit layer is a first area, and the rest is a second area. The surface roughness of the second area is less than or equal to the surface roughness of the first area.
[0027] It can be understood that the first region and the second region are both located on the surface of the dielectric layer, wherein the first region is located on the surface where the dielectric layer and the adhesive layer are bonded, and the second region can be located only on the surface where the dielectric layer and the adhesive layer are bonded; or, the second region can be located on all surfaces of the dielectric layer except the first region, including the surface where the dielectric layer and the adhesive layer are bonded, the side of the dielectric layer, and the surface of the dielectric layer away from the adhesive layer; or, the second region can also be located on the surface where the dielectric layer and the adhesive layer are bonded and the surface of the dielectric layer away from the adhesive layer.
[0028] In the printed circuit board provided by the present invention, the surface roughness of the second area is less than or equal to 0.5 μm, so that the surface roughness of the first area can be controlled between 0.3 μm and 1.0 μm, which cooperates with the adhesive layer to ensure high peel strength between the dielectric layer and the conductive circuit layer, while reducing the dielectric loss of the printed circuit board.
[0029] In one embodiment, the dielectric layer is formed by curing one or more prepregs, the prepregs comprising a reinforcing material and a dried resin composition attached to the reinforcing material, the resin composition comprising a thermosetting resin, a low-polarity resin, a dielectric filler and a crosslinking agent.
[0030] It is understandable that the solubility parameter of the thermosetting resin is greater than 9. In one embodiment, the thermosetting resin includes at least one of thermosetting polyphenylene ether resin, styrene resin, butadiene resin, acrylonitrile-styrene copolymer, methacrylate-styrene copolymer, acrylonitrile-butadiene-styrene copolymer, hydrogenated styrene-butadiene block copolymer, styrene-butadiene-styrene copolymer, styrene-isoprene-styrene copolymer, styrene-polyolefin-styrene copolymer, styrene-acrylonitrile copolymer, styrene-butadiene rubber or acrylonitrile-butadiene rubber. Considering that the thermosetting polyphenylene ether resin has excellent dielectric properties and heat resistance, and its dielectric properties are very stable with temperature or frequency changes, that is, the dielectric properties of the thermosetting polyphenylene ether resin are very stable and excellent in a wide frequency and high frequency range and in a certain temperature range, it is preferred that the thermosetting resin is selected from the thermosetting polyphenylene ether resin.
[0031] In order to better reduce the polarity of the resin composition and thus reduce the dielectric loss of the dielectric layer, it is further preferred that the thermosetting resin is selected from a vinyl-terminated polyphenylene ether resin. In one embodiment, the molecular formula of the vinyl-terminated polyphenylene ether resin includes 1.2 to 3 vinyl groups, and the molecular weight of the vinyl-terminated polyphenylene ether resin is 800-4000.
[0032] It should be noted that the solubility parameter of the low polarity resin is less than or equal to 9. It can be understood that the solubility parameter refers to 1 cm 3 The square root of the heat of evaporation required to evaporate a liquid. The smaller the value, the lower the polarity.
[0033] In order to further reduce the polarity of the low-polarity resin and thus reduce the dielectric loss of the resin composition, preferably, the molecular formula of the low-polarity resin contains only carbon atoms, hydrogen atoms, fluorine atoms or oxygen atoms. Further preferably, the molecular formula of the low-polarity resin contains only carbon atoms and hydrogen atoms, or only carbon atoms and fluorine atoms. In one embodiment, the molecular weight of the low-polarity resin is 50,000-200,000.
[0034] In one embodiment, the low polarity resin is selected from polyisoprene, polyisoprene hydrogenated compounds, polyisoprene alkyl compounds, polybutadiene, polybutadiene hydrogenated compounds, polybutadiene alkyl compounds, polystyrene butadiene, polystyrene butadiene hydrogenated compounds, polystyrene butadiene alkyl compounds, butyl rubber, butyl rubber hydrogenated compounds, butyl rubber alkyl compounds, ethylene propylene rubber, ethylene propylene rubber hydrogenated compounds, ethylene propylene rubber alkyl compounds, styrene butadiene ethylene, styrene butadiene ethylene hydrogenated compounds, styrene butadiene ethylene alkyl compounds, styrene butadiene styrene, styrene butadiene styrene hydrogenated compounds, styrene butadiene styrene alkyl compounds. The low polarity substance is selected from at least one of fluororubber or its derivatives, silicone rubber, polytetrafluoroethylene or vinyl aromatic compound polymers.
[0035] In one embodiment, the mass ratio of the low polarity resin to the sum of the crosslinking agent and the thermosetting resin is 1:20-1:4.
[0036] In one embodiment, the dielectric filler includes at least one of crystalline silica, fused silica, spherical silica, alumina, titanium dioxide, strontium titanate, barium titanate, boron nitride or aluminum nitride, and the mass fraction of the dielectric filler in the resin composition is 10%-80%.
[0037] The crosslinking agent in the resin composition of the present application is selected from a curing agent that can react with a thermosetting resin to cure the resin composition; in order to better reduce the polarity of the resin composition, thereby reducing the dielectric loss of the dielectric layer, in one embodiment, the structural formula of the crosslinking agent contains only carbon atoms and hydrogen atoms, and the crosslinking agent includes but is not limited to styrene, styrene derivatives, compounds with acryloyl groups in the molecule, compounds with methacryloyl groups in the molecule, compounds with vinyl groups in the molecule, compounds with allyl groups in the molecule, compounds with acenaphthylene structures in the molecule, compounds with maleimide groups in the molecule, or compounds with isocyanurate groups in the molecule. In order to improve the reliability of the resin composition and improve the heat resistance of the dielectric layer, it is further preferred that the structural formula of the crosslinking agent contains an aromatic group.
[0038] In order to improve the reactivity of the cross-linking agent with the thermosetting resin and at the same time, to ensure that the dielectric layer has lower dielectric loss and excellent molding performance, in one embodiment, the molecular weight of the cross-linking agent is 100-3000.
[0039] In one embodiment, the mass ratio of the thermosetting resin to the crosslinking agent is 20:80-80:20. Further, the mass ratio of the thermosetting polyphenylene ether resin to the crosslinking agent is 20:80-80:20.
[0040] In one embodiment, the resin composition also includes an initiator. Specifically, the initiator is selected from peroxides capable of initiating free radical reactions. In one embodiment, the peroxide is selected from at least one of di-tert-butyl peroxide, dilauroyl peroxide, hexadecyl peroxydicarbonate, tetradecyl peroxydicarbonate, dipentyl peroxide, diisopropylbenzene peroxide, bis(tert-butylperoxyisopropyl)benzene, 2,5-dimethyl-2,5-di-tert-butylperoxide hexane, α,α'-di(tert-butylperoxy)diisopropylbenzene, tert-butylperoxideisopropylbenzene or diisopropylbenzene hydroperoxide; the mass fraction of the initiator in the resin composition is 0.005%-5%.
[0041] In one embodiment, the resin composition includes a solvent, and preferably, the solvent includes at least one of toluene or xylene.
[0042] In one embodiment, the thickness of the bonding layer is less than or equal to 1.5 μm. Preferably, the thickness of the bonding layer is less than or equal to 1 μm.
[0043] In order to avoid uneven thickness of the adhesive layer and affect the surface roughness of the printed circuit board, in one embodiment, the thickness deviation of the adhesive layer is less than or equal to 5%. It can be understood that the thickness deviation of the adhesive layer refers to the difference between the thickest and thinnest parts of a single adhesive layer, or the thickness deviation of the adhesive layer between different batches of printed circuit boards.
[0044] It can be understood that the bonding layer can improve the surface hydrophilicity of the dielectric layer. In one embodiment, the material of the bonding layer is selected from at least one of self-assembly resins such as silane coupling agents containing unsaturated double bonds, silane coupling agents containing phenylamino groups, phthalates, aluminates, organic chromium complexes, borides, phosphates, chromates or stannates.
[0045] In the printed circuit board provided by the present invention, the dielectric layer and the conductive circuit layer have high peel strength, and at the same time, the signal transmission loss of the printed circuit board is low; therefore, the printed circuit board of the present invention can well meet application scenarios such as extremely low signal transmission loss.
[0046] The present invention also provides a method for preparing the printed circuit board as described above, comprising the following steps:
[0047] S10, stacking one or more prepregs to form a prepreg layer, covering at least one surface of the prepreg layer with a tool, and removing the tool after curing to obtain a dielectric layer;
[0048] S20, performing micro-nano laser processing on a predetermined area of the dielectric layer to form a first area with a surface roughness of 0.3 μm-1.0 μm;
[0049] S30, forming a bonding layer on the surface of the dielectric layer that has been processed by micro-nano laser; and
[0050] S40, forming a conductive circuit layer at a position directly opposite to the first region to obtain a printed circuit board, wherein the conductive circuit layer is bonded to a surface of the adhesive layer away from the dielectric layer.
[0051] In step S10, the prepreg can be prepared by the following steps: the resin composition is formed on the reinforcing material by coating, impregnation, etc., and then dried or baked.
[0052] In one embodiment, the reinforcing material is selected from glass fiber cloth, and specifically, the glass fiber cloth is selected from 7628 type glass fiber cloth, 2116 type glass fiber cloth, 1080 type glass fiber cloth or 106 type glass fiber cloth.
[0053] It should be noted that the surface roughness of the tool is less than or equal to 0.5μm. Specifically, the roughness of the surface where the tool and the semi-cured layer are bonded is less than or equal to 0.5μm. By controlling the roughness of the surface where the tool and the semi-cured layer are bonded, the surface roughness of the obtained dielectric layer is made less than or equal to 0.5μm.
[0054] In order to better replicate the surface roughness of the mold onto the surface of the semi-cured sheet layer, so as to better make the surface roughness of the dielectric layer less than or equal to 0.5μm, and further form a first region with a surface roughness of 0.3μm-1.0μm, in one embodiment, the hardness of the mold at 50℃-400℃ is greater than or equal to 400HV, and the thickness uniformity of the mold is less than or equal to 0.05mm.
[0055] In one embodiment, the material of the tool is selected from glass or steel plate.
[0056] In order to improve the bonding force between the metal and the dielectric layer, a finer-grained porous structure is introduced on the surface of the dielectric layer to promote the mechanical interlocking behavior of the interface while optimizing the chemical state of the surface of the dielectric layer, thereby improving the adhesion of the subsequent bonding layer and facilitating the directional introduction of the bonding layer. Step S20 includes the following steps: performing micro-nano laser processing on a preset area of the dielectric layer using a pulsed laser, wherein the wavelength of the laser of the pulsed laser is less than or equal to 500nm, and the laser power of the pulsed laser is less than or equal to 15W; preferably, the wavelength of the laser of the pulsed laser is 10nm-400nm, and the laser power of the pulsed laser is 0.1W-15W, preferably 0.1W-10W, and further preferably 0.1W-7.5W.
[0057] In order to improve the uniformity of the thickness of the bonding layer, step S30 includes forming a surface treatment agent on the surface of the dielectric layer that has been treated with micro-nano laser to form the bonding layer.
[0058] The surface roughness of the first region is increased by the micro-nano laser processing in step S20, which cooperates with the adhesive layer formed in step S30 to ensure high peeling strength between the dielectric layer and the conductive circuit layer.
[0059] In order to better improve the uniformity of the conductive circuit layer, step S40 includes forming a conductive circuit layer at a position directly opposite to the first region by using an ion sputtering method.
[0060] The present invention realizes the simple preparation of a printed circuit board having low signal transmission loss and high peeling strength between a dielectric layer and a conductive circuit layer.
[0061] Hereinafter, the printed circuit board and the method for preparing the same will be further described through the following specific embodiments.
[0062] Example 1
[0063] A resin composition is prepared by mixing 60 parts by weight of modified polyphenylene ether (solubility parameter > 9), 15 parts by weight of hydrogenated polyisoprene (solubility parameter is 7), 40 parts by weight of triallyl isocyanurate, 172.59 parts by weight of spherical silica, 0.05 parts by weight of α,α′-di(tert-butylperoxy)diisopropylbenzene and 191.76 parts by weight of xylene.
[0064] The resin composition is coated on 1080 type glass fiber cloth and baked in an oven at 100°C-170°C to obtain a semi-cured sheet, in which the glue content is 60%, wherein the glue content is calculated as follows: glue content = (mass of semi-cured sheet - mass of glass fiber cloth) × 100% / mass of semi-cured sheet.
[0065] Two semi-cured sheets are overlapped to obtain a semi-cured layer, and carbon steel tools with a surface roughness of 0.4 μm are placed on both sides of the semi-cured layer. The semi-cured layer is placed in a vacuum hot press and pressed at 200°C for 2 hours under a pressure of 15MPa-30MPa for curing. The carbon steel tool is removed to obtain a dielectric layer with a surface roughness of 0.4 μm.
[0066] A pulsed laser is used to perform micro-nano laser processing on a preset area of the dielectric layer to form a first area with a surface roughness of 0.8 μm. In the dielectric layer, except for the first area, the rest is the second area, and the surface roughness of the second area is 0.4 μm. The wavelength of the pulsed laser is 380 nm, and the laser power of the pulsed laser is 10 W.
[0067] An ethanol solution and an aminosilane coupling agent are mixed to obtain a surface treatment agent, and the surface treatment agent is formed on the surface of the dielectric layer treated by micro-nano laser to form a bonding layer, wherein the thickness of the bonding layer is 1 μm and the thickness deviation of the bonding layer is 0.04 μm.
[0068] An ion sputtering method is used to form a conductive circuit layer at a position directly opposite to the first region to obtain a printed circuit board, and the conductive circuit layer is bonded to a surface of the adhesive layer away from the dielectric layer.
[0069] Example 2
[0070] Example 2 is carried out with reference to Example 1, except that a pulsed laser is used to perform micro-nano laser processing on a preset area of the dielectric layer to form a first area with a surface roughness of 1 μm, wherein the wavelength of the pulsed laser is selected to be 380 nm, and the laser power of the pulsed laser is 15 W.
[0071] Example 3
[0072] Example 3 is carried out with reference to Example 1, except that a pulsed laser is used to perform micro-nano laser processing on a preset area of the dielectric layer to form a first area with a surface roughness of 0.3 μm, wherein the wavelength of the pulsed laser is selected to be 380 nm, and the laser power of the pulsed laser is 1 W.
[0073] Example 4
[0074] Example 4 was carried out with reference to Example 1, except that the surface roughness of the tool was 0.5 μm and the surface roughness of the second region was 0.5 μm.
[0075] A pulsed laser is used to perform micro-nano laser processing on a preset area of the dielectric layer to form a first area with a surface roughness of 1 μm, wherein the wavelength of the pulsed laser is 380 nm and the laser power of the pulsed laser is 10 W.
[0076] Example 5
[0077] Example 5 is carried out with reference to Example 1, except that the low polarity resin is selected from vinyl aromatic compound polymers and has a solubility parameter of 15.
[0078] Example 6
[0079] Example 6 is carried out in accordance with Example 1, except that the ratio of the sum of the mass of the crosslinking agent and the thermosetting resin to the mass of the low-polarity resin is 20:1.
[0080] Example 7
[0081] Example 7 is carried out with reference to Example 1, except that the ratio of the sum of the mass of the cross-linking agent and the thermosetting resin to the mass of the low-polarity resin is 4:1.
[0082] Example 8
[0083] Example 8 was carried out with reference to Example 1, except that the cross-linking agent was selected from acenaphthylene.
[0084] Example 9
[0085] Example 9 is carried out with reference to Example 1, except that the thermosetting resin is polybutadiene having a solubility parameter greater than 9.
[0086] Example 10
[0087] Example 10 is carried out with reference to Example 1, except that the low-polarity resin is a bismaleimide resin containing nitrogen atoms.
[0088] Comparative Example 1
[0089] A resin composition was prepared by mixing 60 parts by weight of modified polyphenylene ether (solubility parameter > 9), 15 parts by weight of hydrogenated polyisoprene (solubility parameter is 7), 40 parts by weight of triallyl isocyanurate, 172.59 parts by weight of spherical silica, 0.05 parts by weight of α,α'-di(tert-butylperoxy)diisopropylbenzene and 191.76 parts by weight of xylene.
[0090] The resin composition is coated on 1078 quartz glass fiber cloth and baked in an oven at 100°C-170°C to obtain a prepreg, wherein the glue content in the prepreg is 60%, wherein the glue content is calculated as follows: glue content = (mass of prepreg - mass of glass fiber cloth) × 100% / mass of prepreg.
[0091] Two semi-cured sheets are overlapped to obtain a semi-cured layer, and carbon steel tools with a surface roughness of 0.4 μm are placed on both sides of the semi-cured layer. The semi-cured layer is placed in a vacuum hot press and pressed at 200°C for 2 hours under a pressure of 15MPa-30MPa for curing. The carbon steel tool is removed to obtain a dielectric layer with a surface roughness of 0.4 μm.
[0092] An ethanol solution and an aminosilane coupling agent are mixed to obtain a surface treatment agent, and the surface treatment agent is formed on the surface of the dielectric layer treated by micro-nano laser to form a bonding layer, wherein the thickness of the bonding layer is 1 μm and the thickness deviation of the bonding layer is 0.04 μm.
[0093] An ion sputtering method is adopted to form a conductive circuit layer on the surface of the bonding layer away from the dielectric layer to obtain a printed circuit board.
[0094] Comparative Example 2
[0095] A resin composition is prepared by mixing 60 parts by weight of modified polyphenylene ether (solubility parameter > 9), 15 parts by weight of hydrogenated polyisoprene (solubility parameter is 7), 40 parts by weight of triallyl isocyanurate, 172.59 parts by weight of spherical silica, 0.05 parts by weight of α,α′-di(tert-butylperoxy)diisopropylbenzene and 191.76 parts by weight of xylene.
[0096] The resin composition is coated on 1078 quartz glass fiber cloth and baked in an oven at 100°C-170°C to obtain a prepreg, wherein the glue content in the prepreg is 60%, wherein the glue content is calculated as follows: glue content = (mass of prepreg - mass of glass fiber cloth) × 100% / mass of prepreg.
[0097] Two semi-cured sheets are overlapped to obtain a semi-cured layer, and carbon steel tools with a surface roughness of 0.4 μm are placed on both sides of the semi-cured layer. The semi-cured layer is placed in a vacuum hot press and pressed at 200°C for 2 hours under a pressure of 15MPa-30MPa for curing. The carbon steel tool is removed to obtain a dielectric layer with a surface roughness of 0.4 μm.
[0098] A pulsed laser is used to perform micro-nano laser processing on a preset area of the dielectric layer to form a first area with a surface roughness of 0.8 μm. In the dielectric layer, except for the first area, the rest is the second area, and the surface roughness of the second area is 0.4 μm. The wavelength of the pulsed laser is 380 nm, and the laser power of the pulsed laser is 10 W.
[0099] An ion sputtering method is used to form a conductive circuit layer at a position directly opposite to the first area to obtain a printed circuit board.
[0100] Comparative Example 3
[0101] A resin composition is prepared by mixing 60 parts by weight of modified polyphenylene ether (solubility parameter > 9), 15 parts by weight of hydrogenated polyisoprene (solubility parameter is 7), 40 parts by weight of triallyl isocyanurate, 172.59 parts by weight of spherical silica, 0.05 parts by weight of α,α′-di(tert-butylperoxy)diisopropylbenzene and 191.76 parts by weight of xylene.
[0102] The resin composition is coated on 1078 quartz glass fiber cloth and baked in an oven at 100°C-170°C to obtain a prepreg, wherein the glue content in the prepreg is 60%, wherein the glue content is calculated as follows: glue content = (mass of prepreg - mass of glass fiber cloth) × 100% / mass of prepreg.
[0103] Two semi-cured sheets are overlapped to obtain a semi-cured layer, and a carbon steel mold with a surface roughness of 0.2μm is placed on both sides of the semi-cured layer. The semi-cured layer is placed in a vacuum hot press and pressed at a temperature of 200°C for 2 hours under a pressure of 15MPa-30MPa for curing. The carbon steel mold is removed to obtain a dielectric layer with a surface roughness of 0.25μm.
[0104] A pulsed laser is used to perform micro-nano laser processing on a preset area of the dielectric layer to form a first area with a surface roughness of 0.25 μm. In the dielectric layer, except for the first area, the rest is the second area, and the surface roughness of the second area is 0.25 μm. The wavelength of the pulsed laser is 380 nm, and the laser power of the pulsed laser is 0.5 W.
[0105] An ethanol solution and an aminosilane coupling agent are mixed to obtain a surface treatment agent, and the surface treatment agent is formed on the surface of the dielectric layer treated by micro-nano laser to form a bonding layer, wherein the thickness of the bonding layer is 1 μm and the thickness deviation of the bonding layer is 0.04 μm.
[0106] An ion sputtering method is used to form a conductive circuit layer at a position directly opposite to the first region to obtain a printed circuit board, and the conductive circuit layer is bonded to a surface of the adhesive layer away from the dielectric layer.
[0107] Comparative Example 4
[0108] A resin composition is prepared by mixing 60 parts by weight of modified polyphenylene ether (solubility parameter > 9), 15 parts by weight of hydrogenated polyisoprene (solubility parameter is 7), 40 parts by weight of triallyl isocyanurate, 172.59 parts by weight of spherical silica, 0.05 parts by weight of α,α′-di(tert-butylperoxy)diisopropylbenzene and 191.76 parts by weight of xylene.
[0109] The resin composition is coated on 1078 quartz glass fiber cloth and baked in an oven at 100°C-170°C to obtain a prepreg, wherein the glue content in the prepreg is 60%, wherein the glue content is calculated as follows: glue content = (mass of prepreg - mass of glass fiber cloth) × 100% / mass of prepreg.
[0110] Two semi-cured sheets are overlapped to obtain a semi-cured layer, and a carbon steel mold with a surface roughness of 0.5 μm is placed on both sides of the semi-cured layer. The semi-cured layer is placed in a vacuum hot press and pressed at a temperature of 200°C for 2 hours under a pressure of 15MPa-30MPa for curing. The carbon steel mold is removed to obtain a dielectric layer with a surface roughness of 0.5 μm.
[0111] A pulsed laser is used to perform micro-nano laser processing on a preset area of the dielectric layer to form a first area with a surface roughness of 1.5 μm. In the dielectric layer, except for the first area, the rest is the second area, and the surface roughness of the second area is 0.5 μm. The wavelength of the pulsed laser is 380 nm, and the laser power of the pulsed laser is 20 W.
[0112] An ethanol solution and an aminosilane coupling agent are mixed to obtain a surface treatment agent, and the surface treatment agent is formed on the surface of the dielectric layer treated by micro-nano laser to form a bonding layer, wherein the thickness of the bonding layer is 1 μm and the thickness deviation of the bonding layer is 0.04 μm.
[0113] An ion sputtering method is used to form a conductive circuit layer at a position directly opposite to the first region to obtain a printed circuit board, and the conductive circuit layer is bonded to a surface of the adhesive layer away from the dielectric layer.
[0114] The performance tests were performed on the printed circuit boards prepared in Examples 1 to 10 and Comparative Examples 1 to 4. The test methods are shown below. The specific test results are shown in Table 1.
[0115] in,
[0116] Peel strength: Use a peel strength tester to test the peel strength between the dielectric layer and the conductive circuit layer according to IPC-TM-650;
[0117] Dielectric constant test method: According to the stripline test method, the test frequency is 10GHz;
[0118] Transmission loss test method: The conductive line layer on one side of the printed circuit board is processed to form 10 wirings with a line width of 100-300μm, a line length of 1000mm, and a line spacing of 20mm. Two dielectric layers and metal foils are laminated on the surface of one side where the wiring is formed to make a three-layer board. It should be noted that the line width of the wiring is adjusted so that the characteristic impedance of the wiring after the three-layer board is made becomes 50Ω.
[0119] The transmission loss (dB / m) of the wiring formed in the obtained three-layer board at 12.5 GHz was measured using a network analyzer;
[0120] Glass transition temperature (Tg), the test method adopts dynamic thermomechanical analyzer.
[0121] Table 1
[0122]
[0123]
[0124] In Comparative Example 1, since micro-nano laser processing was not performed in the preset area of the dielectric layer, the conductive circuit layer could not adhere to the surface of the adhesive layer, and the conductive circuit layer in the obtained printed circuit board fell off. Therefore, the peel strength and transmission loss between the dielectric layer and the conductive circuit layer in Comparative Example 1 could not be detected.
[0125] The technical features of the above embodiments may be combined arbitrarily. To make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0126] The above embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for those of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A printed circuit board, characterized in that: The printed circuit board comprises a dielectric layer, and an adhesive layer and a conductive circuit layer stacked on at least one surface of the dielectric layer, the area of the dielectric layer facing the conductive circuit layer is a first area, and the rest is a second area, the surface roughness of the first area is 0.3 μm-1.0 μm, the surface roughness of the second area is less than or equal to the surface roughness of the first area, and the surface roughness of the second area is less than or equal to 0.5 μm, wherein the material of the adhesive layer is selected from at least one of a silane coupling agent containing an unsaturated double bond, a silane coupling agent containing an aniline group, a phthalate coupling agent, an aluminate coupling agent, an organic chromium complex coupling agent, a boride, a phosphate, a chromate coupling agent, or a stannate coupling agent; The dielectric layer is formed by curing one or more semi-cured sheets, and the semi-cured sheets include a reinforcing material and a dried resin composition attached to the reinforcing material. The resin composition includes a thermosetting resin, a low-polarity resin, a dielectric filler and a cross-linking agent. The solubility parameter of the low-polarity resin is less than or equal to 9, the solubility parameter of the thermosetting resin is greater than 9, and the ratio of the sum of the mass of the cross-linking agent and the thermosetting resin to the mass of the low-polarity resin is 20:1-4:
1.
2. The printed circuit board according to claim 1, characterized in that: The low polarity resin is selected from the group consisting of polyisoprene, polyisoprene hydrogenated compounds, polyisoprene alkyl compounds, polybutadiene, polybutadiene hydrogenated compounds, polybutadiene alkyl compounds, polystyrene butadiene, polystyrene butadiene hydrogenated compounds, polystyrene butadiene alkyl compounds, butyl rubber, butyl rubber hydrogenated compounds, butyl rubber alkyl compounds, ethylene propylene rubber, ethylene propylene rubber hydrogenated compounds, ethylene propylene rubber alkyl compounds, styrene butadiene ethylene, styrene butadiene ethylene hydrogenated compounds, styrene butadiene ethylene alkyl compounds, styrene butadiene styrene, styrene butadiene styrene hydrogenated compounds, styrene butadiene styrene alkyl compounds, styrene isoprene styrene, styrene isoprene styrene hydrogenated compounds, styrene isoprene styrene alkyl compounds, styrene ethylene butylene styrene, styrene ethylene butylene styrene hydrogenated compounds, styrene ethylene butylene styrene alkyl compounds, styrene propylene styrene, styrene propylene styrene hydrogenated compounds, styrene propylene styrene alkyl compounds, styrene ethylene propylene styrene, styrene ethylene propylene styrene hydrogenated compounds, and styrene ethylene propylene styrene alkyl compounds; Alternatively, the low-polarity resin is selected from at least one of fluororubber or its derivatives, silicone rubber, polytetrafluoroethylene or vinyl aromatic compound polymers.
3. The printed circuit board according to claim 1, characterized in that: The thermosetting resin is selected from at least one of thermosetting polyphenylene ether resin, styrene resin, butadiene resin, acrylonitrile-styrene copolymer, methacrylate-styrene copolymer, acrylonitrile-butadiene-styrene copolymer, hydrogenated styrene-butadiene block copolymer, styrene-butadiene-styrene copolymer, styrene-isoprene-styrene copolymer, styrene-polyolefin-styrene copolymer, styrene-acrylonitrile copolymer, styrene-butadiene rubber or nitrile rubber; And / or, the mass ratio of the thermosetting resin to the cross-linking agent is 20:80-80:
20.
4. The printed circuit board according to claim 1, characterized in that: The thickness of the bonding layer is less than or equal to 1.5 μm.
5. The printed circuit board according to any one of claims 1 to 4, characterized in that: The thickness deviation of the bonding layer is less than or equal to 5%.
6. A method for preparing a printed circuit board according to any one of claims 1 to 5, characterized in that: The following steps are involved: Laminating one or more prepregs to form a prepreg layer, covering at least one surface of the prepreg layer with a tool having a surface roughness of less than or equal to 0.5 μm, and removing the tool after curing to obtain a dielectric layer; Performing micro-nano laser processing on a predetermined area of the dielectric layer to form a first area with a surface roughness of 0.3 μm-1.0 μm; forming a bonding layer on the surface of the dielectric layer treated by micro-nano laser; as well as A conductive circuit layer is formed at a position directly opposite to the first region to obtain a printed circuit board, wherein the conductive circuit layer is bonded to a surface of the adhesive layer away from the dielectric layer.
7. The method for preparing a printed circuit board according to claim 6, characterized in that: The step of performing micro-nano laser processing on the preset area of the dielectric layer includes performing micro-nano laser processing on the preset area of the dielectric layer using a pulsed laser, wherein the wavelength of the laser of the pulsed laser is less than or equal to 500nm, and the laser power of the pulsed laser is less than or equal to 15W.
8. The method for preparing a printed circuit board according to claim 7, characterized in that: The step of forming a conductive circuit layer at a position directly opposite to the first region includes forming a conductive circuit layer at a position directly opposite to the first region by using an ion sputtering method.
